Research Progress on Natural Products' Therapeutic Effects on Atrial Fibrillation by Regulating Ion Channels. (22nd March 2022) - He, Jinshan; Li, Sicong; Ding, Yumeng; Tong, Yujia; Li, Xuebin
Abstract : Antiarrhythmic drugs (AADs) have a therapeutic effect on atrial fibrillation (AF) by regulating the function of ion channels. However, several adverse effects and high recurrence rates after drug withdrawal seriously affect patients' medication compliance and clinical prognosis. Thus, safer and more effective drugs are urgently needed. Active components extracted from natural products are potential choices for AF therapy. Natural products like Panax notoginseng (Burk.) F.H. Chen, Sophora flavescens Ait., Stephania tetrandra S. Moore., Pueraria lobata (Willd.) Ohwi var. thomsonii (Benth.) Vaniot der Maesen., and Coptis chinensis Franch. have a long history in the treatment of arrhythmia, myocardial infarction, stroke, and heart failure in China. Based on the classification of chemical structures, this article discussed the natural product components' therapeutic effects on atrial fibrillation by regulating ion channels, connexins, and expression of related genes, in order to provide a reference for development of therapeutic drugs for atrial fibrillation.